2004
DOI: 10.1210/en.2003-1310
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of Interleukin-1-Induced Transcription of cox-2 and il-8 in Cultured Human Myometrial Cells

Abstract: The specific binding of transcription factors to DNA has been shown to be inhibited by chromatin structure and increased by cooperative interactions with other proteins. Consequently, in situ analysis using chromatin immunoprecipitation offers the most accurate view of transcriptional control. Transient transfection studies and in vitro analyses of IL-1-induced cox-2 transcription in a number of cell types have indicated regulation by either nuclear factor kappa B (NF-kappa B) or CCAAT/enhancer binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 40 publications
6
43
0
1
Order By: Relevance
“…It is well established that IL-1b is a major activator of the crucial and rate-determining enzyme in prostaglandin biosynthesis (PTGS2, also called COX-2; Rauk & Chiao 2000). This action is likely mediated by the nuclear factor NFkB (Ackerman et al 2004, Soloff et al 2004. In agreement with these data, expression of PTGS2 and NFkB genes is strongly induced by IL-1b (7.9-and 10.9-fold increase for PTGS2 and NFkB respectively).…”
Section: Discussionsupporting
confidence: 56%
“…It is well established that IL-1b is a major activator of the crucial and rate-determining enzyme in prostaglandin biosynthesis (PTGS2, also called COX-2; Rauk & Chiao 2000). This action is likely mediated by the nuclear factor NFkB (Ackerman et al 2004, Soloff et al 2004. In agreement with these data, expression of PTGS2 and NFkB genes is strongly induced by IL-1b (7.9-and 10.9-fold increase for PTGS2 and NFkB respectively).…”
Section: Discussionsupporting
confidence: 56%
“…NF-kB inhibition by SASP does, however, repress secretory type II phospholipase A 2 (an enzyme upstream of COX-2 in the PG biosynthetic pathway) in gestational tissues (Lappas et al 2004), as does NF-kB inhibition by NAC (Lappas et al 2003). The in situ binding of the p65 NF-kB subunit to the COX-2 promoter has been demonstrated in IL-1b-stimulated myometrial cells by chromatin immunoprecipitation (Soloff et al 2004). Treatment of myometrial cells with proteasome inhibitors, a COX-2-derived PG metabolite, or a more selective IKKb inhibitor, all of which block NF-kB activity, inhibits IL-1b-induced COX-2 expression and PG synthesis (Belt et al 1999, Lindstrom & Bennett 2005.…”
Section: Nf-kb Is Required For Prostaglandin Synthesismentioning
confidence: 98%
“…Repression of NF-kB DNAbinding by the anti-inflammatory agent sulfasalazine (SASP) or the anti-oxidant N-acetyl-cysteine (NAC) inhibits the release of IL-6, IL-8 and TNF-a from LPS-treated placental, choriodecidual and amnion explants (Lappas et al 2002, Lappas et al 2003. Soloff et al (2004) recently reported the in situ binding of the p65 NF-kB subunit to the endogenous IL-8 promoter in IL-1b-stimulated myometrial cells. Reporter studies in amnion and cervical cells demonstrated that the NF-kB response element is required for transcription of the IL-8 gene in these cells (Elliott et al 2001).…”
Section: Nf-kb Is Activated By and Regulates Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…The human COX-2 gene contains two well-characterized NF-κB response elements in its promoter that bind NF-κB in vitro and in vivo [75][76][77]. In studies using human myometrial cells in culture, we found using chromatin immunoprecipitation (ChIP) that the effects of IL-1β to stimulate recruitment of NF-κB p65 to both proximal and distal NF-κB elements of the COX-2 promoter were markedly diminished by co-incubation with progesterone [72].…”
Section: Pr As a Potential Inhibitor Of Nf-κb-mediated Breast Tumorigmentioning
confidence: 99%